The virtual pilgrimage: the disappearing body from place to space - MacMillen, Sarah (The journal of religion & society, 2011)
This paper explores the phenomenological and metaphysical implications of the increasing abstraction of online religion away from place into space within techgnosis a form of Gnosticism inherent in modernity. In the phenomenon of "virtual pilgrimages" the location of the religious is transposed from its location in "body and place" to the "mind in space." Drawing on theology and philosophy, the author concludes that this phenomenon is a consequence of capitalist modernity. While pilgrimage has traditionally been fastened to a "center," the virtual pilgrimage emerges, from utility-driven space. Echoing Marx's critique, the solid sacred center (place) melts into air (space).